Optimization of Multistep Cavity Configuration to Extend Absorption Bandwidth of Micro Perforated Panel Absorber - FALSAFI, Iman; OHADI, Abdolreza (Archives of Acoustics, 2018)
Micro perforated panel (MPP) absorber is a new form of acoustic absorbing material in comparison with porous ones. These absorbers are considered as next generation ones and the best alternative for traditional porous materials like foams. MPP combined with a uniform air gap constructs an absorber which has high absorption but in a narrow bandwidth of frequency. This characteristic makes MPPAs insufficient for practical purposes in comparison with porous materials. In this study instead of using a uniform air gap behind the MPP, the cavity is divided into several partitions with different depth arrangement which have parallel faces. This method improves the absorption bandwidth to reach the looked for goal. To achieve theoretical absorption of this absorber, equivalent electro-acoustic circuit and Maa’s theory (Maa, 1998) are employed. Maa suggested formulas to calculate MPP’s impedance which show good match with experimental results carried out in previous studies. Electro-acoustic analogy is used to combine MPP’s impedance with acoustic impedances of complex partitioned cavity. To verify the theoretical analyses, constructed samples are experimentally tested via impedance tube. To establish the test, a multi-depth setup facing a MPP is inserted into impedance tube and the absorption coefficient is examined in the 63–1600 Hz frequency range. Theoretical results show good agreement compared to measured data, by which a conclusion can be made that partitioning the cavity behind MPP into different depths will improve absorption bandwidth and the electro-acoustic analogy is an appropriate theoretical method for absorption enhancement research, although an optimisation process is needed to achieve best results to prove the capability of this absorber. The optimisation process provides maximum possible absorption in a desired frequency range for a specified cavity configuration by giving the proper cavity depths. In this article numerical optimisation has been done to find cavity depths for a unique MPP.